Performance and Blood Chemistry as Affected by Inclusion of Moringa Oleifera Leaf Meal in Broiler chicks Diet - M.A. El Tazi, Safa; M. Tibin1, Ibrahim (Journal of Veterinary Medicine and Animal Production, 2022)
U. of K. J. Vet. Med. Anim. Prod., Vol. 5, Issue 2 (2014) p 58-65 ISSN: 243456 58 Performance and Blood Chemistry as Affected by Inclusion of Moringa Oleifera Leaf Meal in Broiler chicks Diet Safa M.A. El Tazi* and Ibrahim M. Tibin1 Abstract The effect of Moringa oleifera leaf meal (MOLM) on the performance and blood chemistry of broiler chicks’ diets were investigated. A total of one-hundred and sixty one-day old, unsexed (Ross) broiler chicks were randomly divided into four experimental groups. Each group was further subdivided into five replicates at the rate of eight chicks per pen in randomized complete block design. Four levels of Moringa oleifera leaf meal (0.0, 3, 5 and 7%) were fed during the experimental period for 7-weeks duration. Birds fed on MOLM gained significantly (P<0.05) higher weight and superior feed conversion ratio than birds fed the control diet. No significant difference between birds fed on 3% & 5% (MOLM) diets regarding final body weight or body weight gain .Birds fed on (5% MOLM) diet showed the heaviest body weight, highest total feed intake with the best feed conversion ratio. There were significant (P<0.05) differences among groups in packed cell volume (PCV) and red blood cell (RBC) of the birds. The haemoglobin (HB), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC) counts showed no significant (P>0.05) difference among treatments. There were significant (P<0.05) differences in the values of total protein supplementary serum, while there were no significant (P>0.05) differences in the values of serum albumin and globulin. Birds fed on (5% MOLM) diet showed the highest values of (PCV), (RBC) and serum total protein as compared to other experimental treatments. The highest profitability ratio (1.47) was obtained by the diet with 5% (MOLM). Moringa oleifera leaf meal could be included at 5% dietary level without any deterious effect on performance and blood characteristics of broilers